Mineral element composition in Antirrhinum subsection Streptosepalum (Plantaginaceae) in Western Europe (Iberian Peninsula). - García-Barriuso, Mónica; L. Crespí, Antonio; Nabais, Cristina; Bernardos, Sonia; Amich, Francisco (Lazaroa, 2012)
Antirrhinum rothmaleri (Pinto da Silva) Amich, Bernardos & García-Barriuso is a restricted and threatened endemic plant that inhabits the serpentines present in northern Portugal. Antirrhinum braun-blanquetii Rothm. and A. meonanthum Hoffmanns. & Link are also plants endemic to the western part of the Iberian Peninsula. Particulate trace concentrations of eight metals (Ba, Co, Cr, Cu, Ni, Pb, Sr and Zn) and ten major elements (Al, Ca, Fe, K, Mg, Mn, Na, P, Si and Ti) were determined in rock samples and dry leaf matter from these three species, belonging to the section Streptosepalum Rothm. of the genus Antirrhinum L. (Plantaginaceae). The habitat and ecology of A. rothmaleri are clearly reflected in its trace metal accumulation. These plants appear to be perfectly adapted to soils developed from different types of ophiolitic bedrock, whose chemical and physical properties have long been known to produce an environment hostile to most plant life. The clear morphological differences between A. rothmaleri and A. braun-blanquetii and A. meonanthum, probably reflect phenomena of genetic divergence and reproductive isolation rather than the nutritional imbalances and toxicity of the ultrabasic soil and rock where A. rothmaleri grows.